Superconvergence of a Galerkin FEM for Higher-Order Elements in Convection-Diffusion Problems. Issue 3 (August 2014) - Franz, Sebastian; Roos, H.-G.
Abstract: In this paper we present a first supercloseness analysis for higher-order Galerkin FEM applied to a singularly perturbed convection-diffusion problem. Using a solution decomposition and a special representation of our finite element space, we are able to prove a supercloseness property of p + 1/4 in the energy norm where the polynomial order p ≥ 3 is odd.